[Block "P"/Rally - Cal Poly vs San Francisco State on October 18, 1947] - [Don Mill?]::::::photographer::: (1947)
Students Gil Brown (with megaphone) and Jack Spaulding at a Cal Poly vs San Francisco State game on October 18, 1947.